Budget impact analysis of breast cancer medications: a systematic review - Ghader Mohammadnezhad; Melika Sattarpour; Najmeh Moradi (Taylor & Francis Group, 2022)
Background Breast cancer (BC) is the most common cancer globally among women, with 2,261,419 new cases in 2020; systemic treatment may be neo-adjuvant, adjuvant, or both. BC subtype guides the standard systemic therapy administered, which consists of endocrine therapy for all HR + tumors, trastuzumab-based HER2-directed antibody therapy plus chemotherapy for all HER2 + tumors (with endocrine therapy given in addition, if concurrent HR positivity), and chemotherapy alone for the triple-negative subtype. This study aimed to identify, evaluate, and systematically review all budget impact analyses (BIAs) of BC medications worldwide. Methods PubMed, Scopus, and Web of Science Core Collection databases were thoroughly searched up to 26th March 2022 to identify original published studies which evaluate BIA of BC medications. ISPOR Task Force guidelines were used to assess the quality of included studies. This study was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results In total, 17 BIAs were included in the study. About half of the studies were conducted in Europe. The results of the BIAs showed that most of the included BIAs are conducted from the payer's perspective; they have different methodological frameworks for recommended chemotherapy, targeted therapy, and immunotherapy agents to treat BC. For the same medications, the results of budgetary effects are not consistent in diverse countries. Nine out of the 17 studies were focused on trastuzumab, in which the biosimilar form reduced costs, but the brand form increased costs, especially in a 52-week treatment period. Conclusion Researchers should conduct the budget impact analysis of high-value medications such as anti-tumor drugs more objectively, and the accuracy of parameters needs to be more strictly guaranteed. Furthermore, it is worthy of declaring that the budgetary impact of the same drug is not always consistent over time, so the researchers should measure access to medication in the long run.